(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to clarify the theoretical concepts of both organizational justice and organizational excellence. Also, to identify the importance of organizational justice in achieving organizational excellence and identify the task of organizational justice in achieving organizational excellence. The research has been applied at Baghdad University. (50) Questionnaire forms were distributed for the purposes of the researcher have adopted a descriptive analytical approach. The study concluded several points. The most important of which is that the administration of Baghdad University depends heavily on distributive justice and procedural and interactive justice in achieving organizational excellence in the university. It was found through research and study that there is a statistically significant correlation between distributive justice and procedural and interactive justice in institutional excellence. The most significant of which is the management of University of Baghdad depends heavily on distributive justice and proceeds and interactive justice in achieving organizational excellence in the university.